Implementation Kalyna Algorithm in Microcontroller - Bilenko, Volodymyr; Hlukhov, Valerii (Advances in Cyber-Physical Systems, 2021)
The information security is playing an increasingly important role nowadays. Therefore, virus can be transmitted through the information in encrypted form. This is also applied to embedded systems. In this regard, the article is assigned to the topic of cryptocurrency protection in embedded systems using the national Ukrainian standard Kalyna. To further explore the topic, this algorithm was implemented on a microcontroller to test the performance, convenience and prospects for usage in embedded systems.